 Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

1.IF Pth term of an A.P is q and qth tem of an AP is p then prove that (p+q) term is 0

8 years ago

let a & d are the first term & common differnece respectively then

pth term = a+(p-1)d = q                       ...............1

qth term = a+(q-1)d = p                     ...............2

1-2

q-p = (p-q)d

d=-1

now

(p+q)th term = a + (p+q-1)d

putting value of a from eq 1

(p+q)th term = q - (p-1)d + (p+q-1)d                  (d =-1)

=0

8 years ago

The pth term of an AP is = a+(p-1)d

where a is the first term of the AP and  d is the common difference

as pth term is equal to q therefore q=a+(p-1)d .....1

similarly qth term is equal to p

p=a+(q-1)d .......2

solve the two equations to get the value of a and d. It will come

a=p+q-1

d=-1

now (p+q)th term is =a+(p+q-1)d

put the values of a and d

=(p+q-1)+(p+q-1)(-1)

=(p+q-1)-(p+q-1)

=0

8 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies

Other Related Questions on Algebra

View all Questions »  Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions